Experience, Deconstruction, Implementation: EDI; A New Approach to Reflective Writing for Academic Purpose. Issue 5 (3rd September 2021) - Clarke, Nicola M.
ABSTRACT: This paper presents a framework for reflective writing specifically for academic purpose, offering a new contribution to the already established literature on reflection. Reflection is a notion that is fundamental to the development of emotional intelligence in our nurses and healthcare practitioners, with nursing curriculums designed to assess our students' ability to reflect. However, due to the use of the current reflective cycles and frameworks already positioned in the literature as structures for reflective writing for academic purpose, our students are finding reflective writing for academic purpose challenging. This paper therefore presents a discourse of the pedagogical practices of teaching reflection that offers amendments required to support a more naturalised embedding of reflection within the health curriculum, in particular the way in which we use reflection and reflective writing as a mode of assessment. The discussion advises on how best to support our nursing and allied health students, offering an alternative perspective on the role reflection plays in the curriculum. Most importantly, this paper presents a new unique framework for reflective writing for academic purpose: 'Experience, Deconstruction, Implementation' (EDI), which will support students in engaging more appropriately with reflection while naturalising the development of critical, analytical thinking.